Non-invasive methods in the identification of selected writing fluids from late 19th and early 20th century - Agata Kłos (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
This article discusses the research project for a master degree dissertation. The object of the study was to assess the efficacy of selected non-invasive optical and spectrometric methods in theidentification of writing inks introduced during the Industrial Revolution. The work was undertaken in order to develop a standard procedure for analyzing late 19th and early 20th century inks that would help to apply efficient and safe conservation treatment for historic documents.